Genetic predisposition to neural crest-derived tumors: revisiting the role of KIF1B. Issue 10 (October 2020) - Cardot Bauters, Catherine; Leteurtre, Emmanuelle; Carnaille, Bruno; Do Cao, Christine; Espiard, Stéphanie; Penven, Malo; Destailleur, Evelyne; Szuster, Isabelle; Lovecchio, Tonio; Leclerc, Julie; Frénois, Fredéric; Esquivel, Emmanuel; et al.
Abstract : Objective: We previously described a family in which predisposition to pheochromocytoma (PCC) segregates with a germline heterozygous KIF1B nucleotide variant (c.4442G>A, p.Ser1481Asn) in three generations. During the clinical follow-up, one proband's brother, negative for the KIF1B nucleotide variant, developed a bilateral PCC at 31 years. This prompted us to reconsider the genetic analysis. Design and methods: Germline DNA was analyzed by next-generation sequencing (NGS) using a multi-gene panel plus MLPA or by whole exome sequencing (WES). Tumor-derived DNA was analyzed by SnapShot, Sanger sequencing or NGS to identify loss-of-heterozygosity (LOH) or additional somatic mutations. Results: A germline heterozygous variant of unknown significance in MAX (c.145T>C, p.Ser49Pro) was identified in the proband's brother. Loss of the wild-type MAX allele occurred in his PCCs thus demonstrating that this variant was responsible for the bilateral PCC in this patient. The proband and her affected grandfather also carried the MAX variant but no second hit could be found at the somatic level. No other pathogenic mutations were detected in 36 genes predisposing to familial PCC/PGL or familial cancers by WES of the proband germline. Germline variants detected in other genes, TFAP2E and TMEM214, may contribute to the multiple tumors of the proband. Conclusion: In this family, the heritability of PCC is linked to the MAX germline variant and not to the KIF1B germline variant which, however, may have contributed to the occurrence of neuroblastoma (NB) in the proband.